THE RELATIONSHIP BETWEEN THE EFFICIENCY OF LABOR RESOURCE UTILIZATION AND UNEMPLOYMENT INDICATORS. - Ozod Sharifullaev, Asliddin Oʻralov (Recent scientific discoveries and methodological research, 2025)
This article illuminates the concept of unemployment, its historical formation process, and its economic substance. Methods for measuring the unemployment rate are discussed, and the relationship between unemployment and economic growth is analyzed based on Okun's law. Furthermore, based on data from the International Labour Organization, the unemployment rate for the world and its regions, as well as the state of the labor market in the Republic of Uzbekistan for 2023–2025, are analytically presented.